The highly conserved domain of RND multidrug efflux pumps in pathogenic Gram-negative bacteria - Shahini Shams Abadi, Milad; Gholipour, Abolfazl; Hadi, Nahal (Cellular and Molecular Biology, 2018)
RND (Resistance-Nodulation-Division) family transporters have a vital role in both intrinsic and acquired multi-drug resistance in Gram-negative bacteria. It is important to find a conserved domain in the RND family between different pathogenic bacteria for diagnostic and therapeutic purpose. Total sequences of three-component system RND efflux pumps were retrieved from NCBI nucleotide and protein database and were subjected to conservation and variation analysis using the multiple sequence alignment feature of the CLC workbench. The phylogenetic tree for main transporters was drawn and the three-dimensional structure was also evaluated. From the sequence conservation analysis, highly conserved residues with 282 base pair (94 amino acid) long were identified. The location of the highly conserved domain is positioned in the domain 1 crystallographic structure of AcrB Escherichia coli and MexB Pseudomonas aeruginosa. The main transporter component phylogenetic tree shows the clusters of diï¬€erent genotypes and their evolutionary association. Each of three components of RND proteins is crucial for drug efflux, and the absence of even one component makes the entire complex totally nonfunctional. Therefore, this highly conserved region can be used to disable the RND multidrug efflux pumps. In addition, this highly conserved can also be used for diagnostic aspects.